The road to excellence: deliberate practice and the development of expertise - Ward, P.; Hodges, N. J.; Starkes, J. L.; Williams, A. M. (High Ability Studies, 2007)
The relative contribution of domain-specific and non-domain-specific activities to the development of soccer expertise was examined using a retrospective cross-sectional design. Elite and subelite players aged between 9 and 18 years of age completed a participation history questionnaire under supervision. Weekly and accumulated hours spent in soccer team practice most consistently discriminated between skill levels across age cohorts. Elite players spent more time in decisionmaking activities during team practice, possessed higher levels of motivation and had greater parental support. Maturational indices, time spent in playful activities, sporting diversity and time at which specialization occurred did not differentiate between groups. Engaging in activities deliberately designed to improve performance rather than mere experience within the domain or experience of related activities is likely to lead to elite status.